Исследования Крымской археологической экспедиции МГУ в окрестностях г. Евпатория в 2008 г. - Егорова, Т.В.; Попова, Е.А.; Коваленко, С.А.; Беловинцева, Н.И. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the research of Chayka hill-fort which revealed four building periods dated from the middle of the 4th c. BC to the 1st c. AD. Besides, the publication presents the results of the ongoing research of the mound 36 at the necropolis near the urban type settlement of Zaozerne.